WOUND CARE MANAGEMENT POST EARTHQUAKE : A SCOPING REVIEW - Devi Harmita (Indonesian Journal of Nursing Scientific, 2024)
Earthquakes can result in various types of injury or injury to the victims. The most common injuries are bruises or abrasions, followed by lacerations, and fractures.This article aims to review the current evidence on wound care management post earthquake. The literature search conducted a scoping review was to use the PRISMA guidelines and the Cochrane Handbook. We conducted a scoping review in PubMed, ScienceDirect, Wiley, Proquest, dan juga EBSCHOST. Searching terms included ―Wound Care Management‖ and ―Injury‖ and ―Earthquake‖ were used. Inclusion criteria Full text, publication of the last 10 years and in English. A total of 10 artikel was selected in the analysis. Article discusses wound care management. We discussed the issue of wound care management after the occurrence of an earthquake disaster related to the type of injury or trauma, how the evacuation process, the methods used in wound management, and preventing complications. This review specifies a summary of wound care management post earthquake. Type injuty or trauma and the methods used in the management of post-earthquake wound care.